Evaluation on the Cost of Energy Transition: A Case Study of Fujian, China - Lin, Changyong; Li, Yuanfei; Cai, Qiyuan; Shi, Pengjia; Song, Malin; Wu, Wei (Frontiers in Energy Research, 2021)
The development of renewable energy in Fujian province has entered a bottleneck period in recent years. Considering the impact of COVID-19, how to formulate the provincial energy development strategy based on the 14th Five-year Plan is an important issue that need to be addressed for Fujian. This paper constructs a provincial Computable General Equilibrium model to analyze the cost of energy transition to renewable resources and tries to find a better pathway that integrated into account social efficiency and cost. The simulation results show that after the implementation of energy substitution, the actual electricity price will increase by about 1.6% and the electricity consumption in various sectors will also decrease, especially in the secondary industry. Overall, the marginal impact of energy substitution on the economy is significant.